THE RATIONALE FOR DIAGNOSTIC AND TREATMENT TACTICS IN PATIENTS WITH NEUROENDOCRINE TUMORS OF THE SMALL INTESTINE - P. N. Romashchenko; N. A. Maistrenko; R. V. Orlova; M. V. Lysanyuk (Вестник хирургии имени И.И. Грекова)
The  OBJECTIVE  of the  study  was  to clarify the  rational  program of diagnosis and  choice  of treatment tactics  for patients with neuroendocrine tumors  (NET) of the  small  intestine, taking  into account their clinical and  morphological characteristics. MATERIAL AND METHODS.  We  studied the  results of examination and  treatment of 39  patients. RESULTS.  CT is the main  method of topical  diagnosis, the  sensitivity  of which  in the  detection of NET of the  small  intestine is 96.4  %. Sign of  the  localization   of  NET  in  the  small  intestine is  the  tumor  conglomerate of  its  mesentery, which  includes diffuse-infiltrative  and   nodular   variant   of  changes.  The   diffuse-infiltrative  variant   of  tumor   conglomerate  is  characterized   by increased risk  of complicated course of tumor  process.  Cytoreductive surgical  treatment allows  to  increase the  survival rate   of  patients with  generalized NET  of  the  small  intestine in  1.7  times.   CONCLUSION.  Treatment of  patients with NET  of  the  small  intestine should   be  carried   out  in  specialized medical   centers that  have   the  ability  to  implement   a multidisciplinary  approach that  can  significantly  increase the  duration   and  quality  of  life of  patients.